ECM29/proteasome-mediated self-antigen generation by CNS-resident neuroglia promotes regulatory T cell activation - Sheng-Wen Chen; Ying Chu; Chien-Hsin Chu; Xuan-Dieu Thi Pham; Hang Pong Ng; Chin-Lin Guo; Pei-Lin Cheng (Cell Reports)
Summary: Proteasomes generate antigenic peptides presented on cell surfaces—a process that, in neuroglia, is highly responsive to external stimuli. However, the function of the self-antigens presented by CNS parenchymal cells remains unclear. Here, we report that the fidelity of neuroglial self-antigens is crucial to suppress encephalitogenic T cell responses by elevating regulatory T (Treg) cell populations. We demonstrate that loss of the proteasome adaptor protein Ecm29 alters the efficacy and accuracy of antigen generation. Inducible oligodendroglia- or microglia-conditional Ecm29 knockout mice exhibit higher susceptibility to experimental autoimmune encephalomyelitis (EAE) than control counterparts do, coincident with reduced Treg cell populations in the spinal cord. Immunopeptidome profiling identifies self-antigens that modulate myelin-reactive T cell responses. Intraspinal adeno-associated virus (AAV)/Olig001-mediated expression of the self-antigen NDUFA1p ameliorates EAE and expands NDUFA1p-recognizing CD103+CD8+CD122+ Treg cells. Thus, Ecm29/proteasome-controlled, neuroglia-derived self-antigens modulate CNS immune tolerance.